2021
DOI: 10.48550/arxiv.2104.02390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LiFi Through Reconfigurable Intelligent Surfaces: A New Frontier for 6G?

Abstract: Light fidelity (LiFi), which is based on visible light communications (VLC), is celebrated as a cutting-edge technological paradigm that is envisioned to be an indispensable part of 6G systems. Nonetheless, LiFi performance is subject to efficiently overcoming the line-of-sight blockage, whose adverse effect on wireless reception reliability becomes even more pronounced in highly dynamic environments, such as vehicular application scenarios. Meanwhile, reconfigurable intelligent surfaces (RIS) emerged recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…where β(•, •) is the Beta function ( [39], Equation (8.380.1)). It can be concluded that p γ F S (γ F S ) in (7) for…”
Section: Fisher-snedecor F Composite Fading Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where β(•, •) is the Beta function ( [39], Equation (8.380.1)). It can be concluded that p γ F S (γ F S ) in (7) for…”
Section: Fisher-snedecor F Composite Fading Modelmentioning
confidence: 99%
“…Moreover, a comparison between relay-ACs and RIS-ACs is provided in [5]. In [6], mmWave RIS-ACs systems are considered, whereas visible light communication (VLC) RIS-ACs systems are considered in [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although different works propose the integration on RIS in different fields (e.g., Unmanned Aerial Vehicles (UAV) [12]), there is a lack of study on the security properties of this new technology. The integration of RIS with attributes was studied in [30], which particularly focus on the LiFi application of VLC. Here the authors discussed how RIS can improve different PLS properties such as Secrecy capacity, jamming protection, and secure beamforming.…”
Section: Related Workmentioning
confidence: 99%
“…RIS can be well combined with high frequency band communications by creating alternative reflecting path and employing massive elements to enable high gains and reconstruct propagation path towards the target user to avoid blockage. Initial works on RIS-assisted millimeter wave (mmWave), terahertz (THz) [24]- [28], and optical [29] wireless communications are promising. Since the optical wireless communication is mainly limited to LOS propagation and easily impaired by obstacles and geometric misalignment losses, RIS can help to confront non-LOS (NLOS) propagation by creating new links to improve the coverage range and reduce the outage probability.…”
Section: Introductionmentioning
confidence: 99%